2013
DOI: 10.1186/1477-7819-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Primary tracheobronchial mucoepidermoid carcinoma - a retrospective study of 32 patients

Abstract: BackgroundThis retrospective study was designed to investigate the clinical characteristics, diagnosis, treatment and prognosis of primary tracheobronchial mucoepidermoid carcinoma (MEC).MethodsClinical data were retrospectively analyzed from 32 patients with pathologically confirmed primary tracheobronchial MEC between January 1990 and December 2010 at Zhejiang Cancer Hospital. The Kaplan-Meier methods were used to estimate and compare survival rates.ResultsThere were 19 males and 13 females ranging in age fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 12 publications
2
55
1
10
Order By: Relevance
“…Furthermore, although the numbers of patients were limited in previous studies [812, 21, 22, 30], it is easy to observe the trend that the average age of the patients was related to the tumor grade. In our study, we focused on elderly patients of >65 years of age and analyzed the prognostic factors influencing DFS and OS.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, although the numbers of patients were limited in previous studies [812, 21, 22, 30], it is easy to observe the trend that the average age of the patients was related to the tumor grade. In our study, we focused on elderly patients of >65 years of age and analyzed the prognostic factors influencing DFS and OS.…”
Section: Discussionmentioning
confidence: 95%
“…Primary mucoepidermoid carcinoma (MEC) of the tracheobronchial airway is a rare childhood tumor, with fewer than 100 cases reported worldwide and constituting only 0.1–0.2% of primary lung malignancies . In the present study, we report bronchial MEC in a 12‐year‐old boy manifesting pneumothorax.…”
Section: Introductionmentioning
confidence: 81%
“…In their cox regression analysis, histological grade and TNM stage and resectability were significantly associated with prognosis. Other reports described grade and operability as meaningful factors of prognosis [4,20]. In another report, age was also reported as a prognostic factor [22].…”
Section: Discussionmentioning
confidence: 98%
“…A few advanced bronchial MEC cases have been treated as NSCLC in clinical practice [4,14]. We summarized the papers reporting on the treatment and prognosis of pulmonary MEC (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26]. Chin and colleagues examined 41 cases of surgical treatment and reported that 5-year survival rate of high-grade MEC was 53.2% and 5-year survival rate of low grade MEC was 66.7% [17].…”
Section: Discussionmentioning
confidence: 99%